MEMBACA KITAB AL-MUSTASHFA: RESPON TERHADAP KASUS MURTAD DAN KEBEBASAN BERAGAMA DI INDONESIA - Abd.Haris (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
The issue of apostasy in Indonesia is still controversial and widely discussed by the public. Leaving the Islamic religion or moving from one religion to another is closely related to religious law and freedom of religion. Today, cases of apostasy are rife among artists for various reasons. Thus, a question arises, does their status make fun of religion? Or blasphemy against religion? Or part of human rights? This paper seriously reviews the case of changing religions using the Ushul Fiqh approach, especially the work of Al-Mustashfa al-Ghazali. This type of research is library research, and looks at phenomena and facts that occur among artists as figures and idols for Indonesian people. From the analysis conducted, this paper concludes that; first, apostates move from Islam and return to disbelief; secondly theologically that killing apostates is not the right solution and is not in accordance with Islamic norms as a religion of rahmatan lil 'alamin. Third, the verses and hadiths do not indicate any killings, except in the context of the verses whereby the perpetrators of apostasy had the aim/intention to be enemies of Islam. Fourth, artists who apostate must be subject to sanctions according to the rules and regulations that apply in Indonesia